2010
DOI: 10.2746/042516405775314772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a constant rate infusion of lidocaine on the quality of recovery from sevoflurane or isoflurane general anaesthesia in horses

Abstract: Summary Reasons for performing study: Lidocaine constant rate infusions (CRIs) are common as an intraoperative adjunct to general anaesthesia, but their influence on quality of recovery has not been thoroughly determined. Objectives: To determine the effects of an intraoperative i.v. CRI of lidocaine on the quality of recovery from isoflurane or sevoflurane anaesthesia in horses undergoing various surgical procedures, using a modified recovery score system. Hypothesis: The administration of intraoperative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 25 publications
3
80
0
2
Order By: Relevance
“…A potential complication of lidocaine and ketamine anaesthesia is ataxia and excitation during the recovery period. Lidocaine infusions are reported to cause ataxia in the recovery period 29 , while prolonged ketamine infusion may lead to muscle rigidity and excitation 19 . This problem can be overcome by discontinuing the lidocaine infusion 30 min prior to the end of surgery, decreasing the ketamine dose to 65 % after 50 min and discontinuing the ketamine infusion 15-20 min prior to the end of surgery 3,10,29 .…”
Section: Discussionmentioning
confidence: 99%
“…A potential complication of lidocaine and ketamine anaesthesia is ataxia and excitation during the recovery period. Lidocaine infusions are reported to cause ataxia in the recovery period 29 , while prolonged ketamine infusion may lead to muscle rigidity and excitation 19 . This problem can be overcome by discontinuing the lidocaine infusion 30 min prior to the end of surgery, decreasing the ketamine dose to 65 % after 50 min and discontinuing the ketamine infusion 15-20 min prior to the end of surgery 3,10,29 .…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the use of lidocaine fitted well in the multimodal analgesic approach that was used in the current case. On the other hand, Valverde and others (2005) reported that the administration of a lidocaine CRI influences the quality of recovery in horses. Disconnection of the infusion 30 minutes before the end of surgery is recommended to reduce ataxia during the recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have an anaesthetic sparing effect in isoflurane anaesthetised calves (Vesal and others 2011). Lidocaine is suspected to induce ataxia in horses (Valverde and others 2005) but did not show any adverse effect in calves (Vesal and others 2011). It was not considered a major risk in the giraffe as the infusion rate of 33 µg kg/minute was below the studied rate of 50 µg kg/minute in the previously mentioned publications.…”
Section: Discussionmentioning
confidence: 99%